The Position of the Syar-iyah Court in Aceh In the Judicial Power System of the Republic of Indonesia - Ahmad Sujud Murtadlo; Abu Tamrin (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
Aceh's Syar'iyah Court is a subset of the province's General Courts and Religious Courts, established by Law No. 50 of 2009 on the Second Amendment to Law No. 7 of 1989 regarding Religious Courts. According to the judicial authority law's stipulations, special courts may only be established in a single of the Supreme Court's subordinate judicial systems. The Syar'iyah Court, as envisioned by Law No. 50 of 2009, stands in stark contrast to the special court provisions of the Law on Judicial Power. This study employs a qualitative research design, normative approach, and library-based methodology by reviewing relevant books, statutes, regulations, papers, and journals. According to this research, the Syar'iyah Court, as a specialized court, belongs in just one jurisdiction: the Supreme Court. If the Sar'iyah Court is any indication, the Syar'iyah Mahakamah should be treated as a unique religious court because of its expertise in Islamic law.